2007
DOI: 10.1128/jvi.00640-07
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Ovine Prion Diseases by Using Thermolysin-Resistant PrP Sc and Endogenous C2 PrP Fragments

Abstract: Disease-associated PrP fragments produced upon in vitro or in vivo proteolysis can provide significant insight into the causal strain of prion disease. Here we describe a novel molecular strain typing assay that used thermolysin digestion of caudal medulla samples to produce PrP res signatures on Western blots that readily distinguished experimental sheep bovine spongiform encephalopathy (BSE) from classical scrapie. Furthermore, the accumulation of such PrP res species within the cerebellum also appeared to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 44 publications
4
32
1
Order By: Relevance
“…1a) that included classical and 'atypical' BSEs (H-type and L-type), as well as transmissible mink encephalopathy (TME) experimentally transmitted to cattle, showed (i) that the PrP pattern in BSE-H inoculated mice and uninfected mice were similar, in relation to the Chandler Baron & Biacabe, 2007C506M3 Baron & Biacabe, 2007Baron et al, , 2008 absence of transmission of H-type BSE in TgOvPrP4 mice , (ii) that the C2 fragment, of~19 kDa, was predominant in BSE-C, BSE-L and TME, whereas C1 was only present in small amounts, or undetectable. These observations matched with previously reported studies of TSE-infected human, murine and ovine tissues or cellculture models (Chen et al, 1995;Jiménez-Huete et al, 1998;Owen et al, 2007b;Yadavalli et al, 2004). The levels of C2 and of PrP res are known to increase during prion infection (Yadavalli et al, 2004).…”
supporting
confidence: 80%
See 3 more Smart Citations
“…1a) that included classical and 'atypical' BSEs (H-type and L-type), as well as transmissible mink encephalopathy (TME) experimentally transmitted to cattle, showed (i) that the PrP pattern in BSE-H inoculated mice and uninfected mice were similar, in relation to the Chandler Baron & Biacabe, 2007C506M3 Baron & Biacabe, 2007Baron et al, , 2008 absence of transmission of H-type BSE in TgOvPrP4 mice , (ii) that the C2 fragment, of~19 kDa, was predominant in BSE-C, BSE-L and TME, whereas C1 was only present in small amounts, or undetectable. These observations matched with previously reported studies of TSE-infected human, murine and ovine tissues or cellculture models (Chen et al, 1995;Jiménez-Huete et al, 1998;Owen et al, 2007b;Yadavalli et al, 2004). The levels of C2 and of PrP res are known to increase during prion infection (Yadavalli et al, 2004).…”
supporting
confidence: 80%
“…In sheep, immunohistochemistry studies indicated that the N-terminal end of PrP d from BSE and from CH1641, compared with other scrapie sources such as SSBP/1, was more strongly digested (Jeffrey et al, 2006). Consistently, Western blot analyses in sheep recently showed that C2 fragments could be detected in SSBP/1, but not in CH1641 and BSE, when an N-terminal (P4) antibody was used (Owen et al, 2007b). However, the novelty in our study is the description of another endogenous, more C-terminally cleaved, PrP fragment of 14 kDa in its unglycosylated form, which we have called CTF14.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…This lack in information is mostly due to the absence of the PrP Sc high resolution 3D structure. Proteolysis fingerprinting performed on extractive PrP Sc reveals that the N-terminal region is completely accessible to proteases [89]. Furthermore, transgenic mice whose Nterminal PrP domain was deleted, were able to replicate the infectious agent [36,102].…”
Section: Regions Involved In the Structural Changementioning
confidence: 99%